Light-responsive nanochannels based on the supramolecular host–guest system - Quan, Jiaxin; Guo, Ying; Ma, Junkai; Long, Deqing; Wang, Jingjing; Zhang, Liling; Sun, Yong; Dhinakaran, Manivannan Kalavathi; Li, Haibing (Frontiers in Chemistry, 2022)
The light-responsive nanochannel of rhodopsin gained wider research interest from its crucial roles in light-induced biological functions, such as visual signal transduction and energy conversion. Though its poor stability and susceptibility to inactivation in vitro have limited its exploration. How-ever, the fabrication of artificial nanochannels with the properties of physical stability, controllable structure, and easy functional modification becomes a biomimetic system to study the stimulus-responsive gating properties. Typically, light-responsive molecules of azobenzene (Azo), retinal and spiropyran were introduced into nanochannels as the photo-switches, which can change the inner sur-face wettability of nanochannels under the influence of light, this ultimately results in photorespon-sive nature of biomimetic nanochannels. Furthermore, the fine-tuning of its stimuli-responsive proper-ties can be achieved through the introduction of host-guest systems generally combined with a non-covalent bond, and the assembling process is reversible. These host-guest systems have been intro-duced into the nanochannels to form the different functions. Based on the host-guest system of light-responsive reversible interaction, it can not only change the internal surface properties of the na-nochannel and control the recognition and transmission behaviors but also realize the controlled re-lease of a specific host or guest molecules in the nanochannel. At present, macrocyclic host molecules have been introduced into nanochannels including pillararenes, cyclodextrin (CD), and metal-organic frameworks (MOFs). They are introduced into the nanochannel through chemical modification or host-guest assemble methods. Based on the changes in the light-responsive structure of azobenzene, spiropyran, retinal, and others with macrocycle host molecules, the surface charge, hydrophilic and hydrophobic properties of the nanochannel were changed to regulate the ionic and molecular transport. In this paper, the development of photoresponsive host and guest assembled nanochannel systems from design to application are reviewed, and the research prospects and problems of this pho-to-responsive nanochannel membrane are presented.